The Equity Effects of Cadasters in Colombia - Cuesta, Jose (Taylor & Francis, 2022)
Well-functioning cadasters help to secure property rights, make economies perform more efficiently and promote environmental conservation. However, their equity effects are less known. Our study addresses how and to what extent cadasters, and reforms to them, affect equity. The authors address this question through an ex-ante simulation methodology using static partial equilibrium fiscal incidence analysis. We apply it to a recent expansion of the cadaster in Colombia, designed as a deliberate equalization strategy in one of the world’s most unequal countries. This expansion will increase the collection of property taxes paid by previously informal households by about US 22.1 million dollars and their net worth by about US 4,993 million dollars (or about 3.2 and 4.9 percent of their baseline value). However, the expansion of the cadaster will also increase the incidence of poverty (by 0.25 percent points), the poverty gap (by 0.20 percent points) and inequality (by 0.12 percent points of the Gini index), unless generous compensatory interventions are applied. We conclude that equity effects of cadasters are complex and multiple. Policy-wide, compensatory measures are needed to alleviate the immediate impacts on poverty and inequality after the increase in taxes that vulnerable and poor households will likely face following a cadaster reform.